2017
DOI: 10.1038/ncomms15599
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell entropy for accurate estimation of differentiation potency from a cell’s transcriptome

Abstract: The ability to quantify differentiation potential of single cells is a task of critical importance. Here we demonstrate, using over 7,000 single-cell RNA-Seq profiles, that differentiation potency of a single cell can be approximated by computing the signalling promiscuity, or entropy, of a cell's transcriptome in the context of an interaction network, without the need for feature selection. We show that signalling entropy provides a more accurate and robust potency estimate than other entropy-based measures, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
293
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(332 citation statements)
references
References 56 publications
13
293
1
Order By: Relevance
“…Moreover, it remains difficult to distinguish quiescent (non-cycling) adult stem cells with longterm regenerative potential from more specialized cells using existing in silico approaches. While gene expression-based models can potentially overcome these limitations (e.g., transcriptional entropy [18][19][20] , pluripotency-associated gene sets 21 and machine learning strategies 22 ), their relative utility across diverse developmental systems and single-cell sequencing technologies is still unclear.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it remains difficult to distinguish quiescent (non-cycling) adult stem cells with longterm regenerative potential from more specialized cells using existing in silico approaches. While gene expression-based models can potentially overcome these limitations (e.g., transcriptional entropy [18][19][20] , pluripotency-associated gene sets 21 and machine learning strategies 22 ), their relative utility across diverse developmental systems and single-cell sequencing technologies is still unclear.…”
Section: Main Textmentioning
confidence: 99%
“…We sought to identify robust, RNA-based determinants of developmental potential without the need for a priori knowledge of developmental direction or intermediate cell states marking cell fate transitions. Toward this end, we evaluated ~19,000 potential correlates of cell potency in scRNA-seq data, including all available gene sets in the Molecular Signatures Database (n = 17,810) 23 , 896 gene sets covering transcription factor binding sites from ENCODE 24 and ChEA 25 , an mRNA-expression-derived stemness index (mRNAsi) 22 , and three computational techniques that infer stemness as a measure of transcriptional entropy (StemID, SCENT, SLICE [18][19][20]. We also explored the utility of 'gene counts', or the number of detectably expressed genes per cell, which has been anecdotally observed to correlate with differentiation status 26-28 , but not yet comprehensively evaluated (Methods).…”
Section: Rna-based Correlates Of Single-cell Differentiation Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Single cell Energies (scEnergy) were calculated, projected onto UMAP space, and used to infer cell state transition probabilities and lineage relationships. We found that lower energies, while typically associated with committed/differentiated cell states (Jin et al, 2018;Teschendorff and Enver, 2017), are also associated with a quiescent cell state because the known quiescent Bu-HFSC (CD34 + ) population showed the lowest scEnergy of all the skin epithelial cell types ( Figure 3D, 4E, and S4H; see Methods section). Using increasingly robust parameters, which incorporate increasing numbers of UW epidermal cells from each cell state to infer lineage progression, scEpath predicted a near-linear path that originates from the Col17a1 Hi basal cell state that displayed the lowest energy of all interfollicular epidermal cells ( Figure 6E, S12C, and S12G).…”
Section: Pseudotemporal Trajectory and Rna Velocity Analyses Reveal Bmentioning
confidence: 90%
“…Previous studies have suggested that in silico differentiation potency and plasticity of single cells can be approximated by computing the signaling promiscuity of a cell's transcriptome (Teschendorff and Enver, 2017). We developed a similar algorithm to calculate the Cellular Entropy (ξ) of single cells called Cellular Entropy Estimator (CEE) -now a feature that has been incorporated into SoptSC (see Methods).…”
Section: Cellular Entropy and Rna Velocity Predict The Likelihood Of mentioning
confidence: 99%